2016
DOI: 10.1073/pnas.1521265113
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring nanoparticle designs to target cancer based on tumor pathophysiology

Abstract: Nanoparticles can provide significant improvements in the diagnosis and treatment of cancer. How nanoparticle size, shape, and surface chemistry can affect their accumulation, retention, and penetration in tumors remains heavily investigated, because such findings provide guiding principles for engineering optimal nanosystems for tumor targeting. Currently, the experimental focus has been on particle design and not the biological system. Here, we varied tumor volume to determine whether cancer pathophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
166
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(168 citation statements)
references
References 39 publications
2
166
0
Order By: Relevance
“…For example, Chan and co-workers reported that the tumor size can impact the tumor uptake of large AuNPs (15-100 nm). [25] In our studies, we also observed that the targeting efficiency (%IDg −1 ) increased as the tumor size decreased from about 0.5 to 0.05 cm 3 at 1 h p.i. when the NP tumor accumulation was mainly governed by the tumor permeability of the NPs ( Figure S10A,B).…”
supporting
confidence: 74%
“…For example, Chan and co-workers reported that the tumor size can impact the tumor uptake of large AuNPs (15-100 nm). [25] In our studies, we also observed that the targeting efficiency (%IDg −1 ) increased as the tumor size decreased from about 0.5 to 0.05 cm 3 at 1 h p.i. when the NP tumor accumulation was mainly governed by the tumor permeability of the NPs ( Figure S10A,B).…”
supporting
confidence: 74%
“…However, most studies show accumulation in the tumour of 1% or less of the injected dose [8]; the majority of injected materials accumulate in the liver and spleen [9,10]. Recent work has further shown that the pathophysiology of the tumour itself affects the uptake of nanoparticles [11]. The biodistribution of injected particles is highly dependent on their size, shape, and surface chemistry [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…RASSL-engineered T cells showed enhanced migration and localization to tumors injected with CNO slow-release biodegradable microparticles. In the future it may be possible to administer nanoparticle drug delivery systems that can accumulate in tumors without the need for direct injection (83). This is an important proof-of-principle study showing how synthetic biology approaches can help to overcome the natural limits of our immune system.…”
Section: Synthetic Biology Tool Kit: Genetic Components For Programmimentioning
confidence: 99%